Estimation of some heavy metals in leaves of plants exposed to the emissions of generators that operate on gasoline fuel and measurement of chlorophyll content and malonedialdehyde (MDA) (Journal of the College of Basic Education, 2022)
The effect of some of the pollution and hazardous heavy metals on the plant and its transmission to humans and the output of the combustion of gasoline generators heavily used in the city of Baghdad and the extent of its contribution to the city's air pollution. Where the plants careless Lepidium and radish planted the seeds of these plants in pots (Snadin) after the end of the process of growth were exposed leaves of these plants (Lepidium and radish) to generator-powered petrol for five weeks and the duration of exposure to 1 hour each day and then were measured heavy elements including lead, where the highest value of the rate of radish 8 ppm .134 and the lowest value of the rate of 35 .8 ppm while the value of the site control control 0.13 ppm either Lepidium was the highest value 125.5 ppm and the lowest value of the rate ppm 21.3 while the value of the site control 0.12 ppm The nickel element where the highest value of the rate of radish 18.70 ppm and the lowest value of the rate of 18.12 ppm, while the value of the site control control 1.1 ppm either Lepidium was the highest value 11.18 ppm and the lowest value of the rate ppm 11.02 while the value of the site control ppm control 0.8 The copper element where The highest value of the rate of radish .82 ppm 15 and the lowest value of the rate of 14.74 ppm, while the value of the site control control 6.4 ppm either Lepidium was the highest value 14.53 ppm and the lowest value of the rate of 13.84 ppm, while the value of the site control control 5.3 ppm. either cadmium element where the highest value rate radish ppm 5.35 and the lowest value of the rate of 4.02 ppm, while the value of the site control control 0.91 ppm either Lepidium was the highest value 2.8 ppm and the lowest value of the rate ppm 1.94, while the value of the site control control 0.3 ppm. iron element where the highest value of the rate of radish ppm 100.09 and the lowest value for the rate at 100.07 ppm, while the value of the site control control 68.27 ppm either Lepidium was the highest value 88.79 ppm and the lowest value of the rate of 70.14 ppm. While the value of the site control control 54.34 ppm either content chlorophyll was decreasing and this definitive guide to pollution plants where the lowest was value for chlorophyll a plant radish 0.863 ppm and the highest value 14.88 ppm and values ​​of site control 22.93 ppm and the lowest value for chlorophyll b ppm was 0.017 and the highest value The site 6.04 ppm, 12.73 ppm control of either the total chlorophyll was the lowest value 0.883 ppm. The highest value of chlorophyll 20.94 ppm and control site35.64 ppm either Lepidium plant was the highest value of chlorophyll a to him 10.30 ppm and the lowest value 0.293 ppm and site control 10.34 ppm either chlorophyll b was the highest value 1.24ppm and the lowest value 0.06 ppm and site control was 1.27 ppm either chlorophyll total reached its highest value 11.53ppm and the lowest his value was 0.213ppm and control site was 11.65ppm . Malonedialdhayde content has increased has reached the highest value to plant radishes 7.07 nmol / g and the lowest value 3.143 nmol / g and site control was 2.324 nmol / g . Lepidium was the highest value 3.35 nmol / g and the lowest value 1.47 nmol / g and site control was 1.162 nmol / g. samples have been chemically digest using a technique atomic spectrometer Flame for the detection of heavy elements and the results showed the presence of 5 elements of heavy task environmentally is Fe, Cu, Cd, Ni, Pb and concentrations influential according to the measurements The World Health WHO study showed that the generators significant effect on our environment, including the plants, the results showed that the pollutants emitted by gasoline generators effect is obvious to all of the plant Lepidium and radish when she was in a location close to the generator, as well as far from the generator site have found there are significant differences are clear between my experience (generators site and site control) of Through the influence of these pollutants on vegetation characteristics of the plants careless any measure chlorophyll content and Malonedialdhayde .